Case Report: Cranial Vault Reduction Cranioplasty for Severe Hydrocephalus - Suryaningtyas, Wihasto; Parenrengi, Muhammad Arifin (Folia Medica Indonesiana, 2020)
Extreme hydrocephalic macrocephaly is still encountered in developing countries due to delayed treatment, rapidly progressing hydrocephalus and family socioeconomic problems. Reduction cranioplasty was used with several techniques to address the issue. The study aimed to determine the safety and feasibility of barrel-stave technique for reducing the size of extreme hydrocephalic macrocephaly. Three post-diversion patients underwent surgical reconstruction. Children with head circumference more or equal to two standard deviation above mean on given age, no active wound at the area of surgery, presentation of sufficient "potential removable fluid” that allows dura reduction and no active shunt infection were eligible. The surgical procedure includes modified pi, barrel-stave technique, and diversion of the cerebrospinal fluid and subdural collection. Clinical data were recorded. Three patients with age range of 2 month to 2 years old underwent the surgery. Two patients had shunt implanted at least 1 month before the surgery and 1 patient had an ETV procedure 3 months before the reduction. The frontal-occipital circumference before surgery ranged from 50 to 63 cm. The maximum reduction that could be achieved was 15 cm. One patient (2 months old) died within 24 hour due to failure to cope with excessive blood loss. Two patients were followed up for 3 months and 6 months without complications. Reduction cranioplasty using barrel-stave techniques is an option for children with extreme large head that poses a mechanical or cosmetic problem. Risk and pitfalls should be considered and taken care meticulously, especially the age and blood loss.